Emerging Pedagogies developed for higher education from the covid-19 curfew - Liliana Lira López; Alejandro Uribe López (Apertura, 2022)
Presenting the results had the goal was to identify the knowledge obtained by the experience of teachers during the confinement for the pandemic, in the months of January to June 2020. The methodological approach was a mixture of two stages: The first one was quantitative, in which a survey was carried out on a suitable non-random sample on six universities within the country. The second one was qualitative, in which semi-structured interviews were carried out on teachers that have experience on both regular learning and distance learning modes caused by the lockdown. The results, from a systemic perspective on the emergent situation, allowed us to recognize the institutions and teachers as knowledge managers. We can observe how the actors managed to bring balance to their institutional structures, as well as to the teaching and learning processes. Notwithstanding the fact that this research was carried out on private universities and that only the learning experience acquired by the transitioning to distant learning was retrieved, the findings contribute pedagogical field create in the crisis, regarding the efficient learning-oriented measurements and organizational structure.